Medical Education - Reflections for the Future / Khalid Yusoff - Yusoff, Khalid (Universiti Teknologi MARA Cawangan Selangor, 2017)
The practice of medicine, and the training of it, is of course steep in history and tradition. Names such as Hippocrates, Galen and Ibnu Sina come to mind easily. The Islamic civilization substantially contributed to and advanced the medical corpus of the Greek civilization. There was of course the practice of medicine in the Indian and Chinese Civilisation which seemed to have taken their own trajectories. The Age of Reformation and Enlightenment in Europe brought scientific basis into the understanding and treatment of diseases - anatomy, physiology, pharmacology flourished. However, it was Abraham Flexner who revolutionized the medical training and medical education - its methods and purpose - with his 1910 Report [1]. Flexner, a school teacher and not a physician, was commissioned by the Carnegie Foundation to review the then medical schools in America and Canada. He was chosen perhaps for his idea that education should be distinguished by small classes, personal attention and hands-on teaching. He was also persuaded by the ideas propagated by John Dewey - a philosopher and educationist - that learning should be by doing, by solving problems, rather than by rote learning [2]. In the course of his study, he became convinced of the essentiality of science in the training of doctors, incorporating biomedical sciences into the medical curriculum, embracing scientific breakthroughs and its advancement. Hence the curriculum was re-designed, giving greater emphasis to science; very much in line with the German system where Medicine was considered a scientific discipline, where physicians had a thorough training in laboratory investigations before they embarked on clinical training. Through this effort, excellence in medical training was redefined and reaffirmed, leading to the closure of many for-profit proprietary medical schools in America.